PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK SD MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ARTICULATE STORYLINE - Rohimah, Siti Maryam; Nurdiansah, Yusup; Putri, Sarah Anida; Anaya, Salma Nur (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
This research aims to determine the increase in mathematical understanding abilities in class II elementary school students through a problem based learning model assisted by articulate storyline media. The research method used is quasi-experimental research with a pre-test and post-test one group design research design. The research was aimed at class II students at SDN 066 Halimun, Bandung City. The population in this study was all class II students at SDN 066 Halimun. The research sample taken was class II-C as many as 20 people. The data collection techniques used in this research are mathematical ability description tests, observation and documentation. Researchers carried out data analysis by testing hypotheses using SPSS Statistics 26.0 for windows software. Based on the research results, an overview of the learning process using Articulate Storyline media with the problem based learning model is going well. From the results of the hypothesis test, it was concluded that there was a significant difference between the ability to understand mathematical concepts before and after using the problem based learning model assisted by articulate storyline media. There is an increase in students' mathematical understanding ability from the results of the normalized gain test, namely 0.45 with a moderate improvement category.